Rare Occurrence of Inhibitors in Von Willebrand Disease: A Case Report - Kulkarni, Bipin P.; Ghargi, Kirti; Shanmukhaiah, Chandrakala; Shetty, Shrimati D. (Frontiers in Medicine, 2022)
Introduction: Type 3 VWD is the least common but the most severe form of this disease with a prevalence of about 0.5 to 1 per million in Western countries. However, it is as high as 50% of the total number of VWD cases in developing countries, including India, mainly because of high degree of consanguinity in some communities and the underdiagnoses of the milder forms of the disease1-3. Rarely, some patients develop inhibitors to VWF, after which they may develop severe anaphylactic reactions on further exposure to VWF containing factor replacement therapy4,5. The prevalence of inhibitor development in type 3 VWD patients was shown to be in the range of 5.8% to 9.5%6-11. There are no gold standard assays for the quantitation of inhibitors to VWF. Objectives: The objective of this study is to standardize the Bethesda assay for anti-VWF inhibitors and to estimate the VWD inhibitor titre. Patients/Methods: We report two rare cases of type 3 VWD who developed inhibitors against VWF. Results and Conclusions: We could quantitate the VWF inhibitor by standardizing the Bethesda assay for anti-VWF inhibitors.